1998
DOI: 10.1076/ceyr.17.5.506.5191
|View full text |Cite
|
Sign up to set email alerts
|

Self-assessment of the quality of vision: association of questionnaire score with objective clinical tests

Abstract: Overall, the model explains 49% of the variance in the average questionnaire score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 8 publications
2
40
0
Order By: Relevance
“…Near visual acuity (reading) was significantly, albeit modestly, correlated with visual function and trouble with vision. A previous study 33 noted that near visual acuity is a better predictor of patients' trouble with vision than Snellen visual acuity. However, near visual acuity as an outcome measure of cataract surgery has rarely been addressed in the literature.…”
Section: Discussionmentioning
confidence: 96%
“…Near visual acuity (reading) was significantly, albeit modestly, correlated with visual function and trouble with vision. A previous study 33 noted that near visual acuity is a better predictor of patients' trouble with vision than Snellen visual acuity. However, near visual acuity as an outcome measure of cataract surgery has rarely been addressed in the literature.…”
Section: Discussionmentioning
confidence: 96%
“…48 It was administered to patients with different eye diseases, including age-related cataract. The questionnaire consists of 17 questions grouped into 6 subgroups, and each question is rated on a 3-point scale.…”
Section: Quality Of Life and Vision Function Questionnairementioning
confidence: 99%
“…36 Conversely, the Epidemiology of Osteoporosis (EPIDOS) study found that visual acuity was associated with hip fracture risk, but depth perception and contrast sensitivity were not. 37 Several [38][39][40] Similarly, Carta et al 41 showed that near visual acuity and contrast sensitivity were strongly associated with quality of life outcomes on a quality of life/visual function questionnaire in 120 patients with cataract, glaucoma, AMD, branch retinal vein occlusion, presbyopia or minor refractive defects. The relationship between contrast sensitivity loss and such measures of quality of life is unclear.…”
Section: Activities Of Daily Living and Quality Of Lifementioning
confidence: 99%